The mysterious association between adiponectin and endometriosis - Zhao, Yong-Qing; Ren, Yi-Fan; Li, Bing-Bing; Wei, Chao; Yu, Bin (Frontiers in Pharmacology, 2024)
Adiponectin is a pleiotropic cytokine predominantly derived from adipose tissue. In addition to its role in regulating energy metabolism, adiponectin may also be related to estrogen-dependent diseases, and many studies have confirmed its involvement in mediating diverse biological processes, including apoptosis, autophagy, inflammation, angiogenesis, and fibrosis, all of which are related to the pathogenesis of endometriosis. Although many researchers have reported low levels of adiponectin in patients with endometriosis and suggested that it may serve as a protective factor against the development of the disease. Therefore, the purpose of this review was to provide an up-to-date summary of the roles of adiponectin and its downstream cytokines and signaling pathways in the aforementioned biological processes. Further systematic studies on the molecular and cellular mechanisms of action of adiponectin may provide novel insights into the pathophysiology of endometriosis as well as potential therapeutic targets.